A comprehensive approach to the modeling and simulation of ballistic textiles. (15th July 2022) - Kędzierski, Piotr; Morka, Andrzej
Abstract: The paper presents a method of modeling impact-loaded ballistic textiles and its implementation for Twaron CT 709 plain weave fabric. The model developed was applied to simulate the resistance of ballistic packages against a 9 mm Parabellum projectile. The main concept of the proposed method is to model the bending stiffness of textiles by means of doubled membrane-shell elements with appropriately selected elastic properties, and to model the stiffness in the out-of-plane direction by means of a nonlinear contact algorithm. Both ideas are original in relation to generally known solutions. The numerical results obtained were compared with experimental data to verify the ability of the method to estimate the following parameters: depression depth in the backing material, number of perforated and damaged layers, and geometry of deformed projectiles. A satisfactory correlation of the parameters listed was achieved with experimental observations. In particular, the error in prediction of depression depth was less than 10%.